Prevalence of tumors, mandibular prognathism, irreversible pulpitis and complete edentulism in a known population - Asher, Pranav B; Bhoosreddy, Seema; Adil, Muneeb; Sumaida, Sumaida; Salkar, Manjiri; D Pujari, Mohan (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the prevalence of tumors, mandibular prognathism, irreversible pulpitis and complete edentulism in a known population. Material and methods: This study was conducted to assess the prevalence of tumors, mandibular prognathism, irreversible pulpitis and complete edentulism in a known population. The study comprised of 100 subjects. All the subjects had been explained about the procedure and were asked to give consent. All the subjects agreed to give consent and hence all the subjects had been included in the trial. The subjects had been clinically examined. The findings had been noted down and data were analysed using SPSS software. Results: In this study, there were 16 subjects who had tumors. 9 of them had odontogenic tumors and 7 of them had non-odontogenic tumors. Mandibular prognathism was seen in 23 subjects. Irreversible pulpitis was seen in 29 subjects and edentulism was seen in 32 subjects. Hence, the prevalence of tumors, mandibular prognathism, irreversible pulpitis and edentulism in this study was 16%, 23%, 29% and 32%. There were 56 males and 44 females in the study. Conclusion: Based on the results of this study, it can be concluded that the prevalence of tumors, mandibular prognathism, irreversible pulpitis and edentulism was 16%, 23%, 29% and 32%, respectively